Analysis of Determinants of the Price of Banking Stocks Listed on the Indonesia Stock Exchange: Analsisis Determinan Harga Saham Perbankan yang Terdaftar di Bursa Efek Indonesia - Muntahanah, Siti; Nursyafa’ah, Aini; Harsuti; Retnowati, Diah (Procedia of Social Sciences and Humanities, 2022)
This study aims to analyze the factors that influence the stock prices of banks listed on the Indonesia Stock Exchange. These factors consist of Loan To Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Return On Equity (ROE) and Operating Cost of Operating Income (BOPO). This study uses a sample of 24 banks that have been adjusted to the research criteria. Based on panel data regression analysis, it can be explained that LDR has a negative effect on stock prices, CAR has a negative effect on stock prices, ROE has a positive effect on stock prices and BOPO has a negative effect on stock prices.